The Respons Of Pepper Growth (Piper Nigrum. L) Malonan I To The Composition Of Plant Media And Amount Of Segment: Respon Pertumbuhan Stek Lada (Piper Nigrum. L) Malonan I Terhadap Komposisi Media Tanam Dan Jumlah Ruas - Mahdalena; Anis Munandar (Agrifarm : Jurnal Ilmu Pertanian, 2020)
Research on the response of growth of pepper cuttings (Piper nigrum. L) Malonan I to the composition of the planting media and the number of segments aims to determine the effect of the composition of the planting media and the number of segments on the growth of pepper cuttings. The study was conducted for 12 weeks (3 months) from October 2019 - January 2020. The research was carried out in the Agrotechnology Experimental Garden at Widya Gama Mahakam University Samarinda. This research uses factorial randomized block design with 2 factors and is repeated 3 times. The first factor is the number of segments (R) consisting of 3 levels, namely, R1 = 1 segment, R2 = 2 segments, R3 = 3 segments The second factor is the growing media (P) consisting of 3 levels, namely: P0 = Top soil (control) , P1 = Top soil + rice husk with a ratio of 3: 1, P2 = Top soil + cow manure with a ratio of 3: 1, P3 = Top soil + rice husk + cow manure. Expected output is to provide information about the best planting media for the growth of Malonan I pepper cuttings for the community. Provide information about the best number of segments for the growth of Malonan I pepper cuttings for the community.